Stakeholder Interaction in the Redesign and Creation of Digital Public Services: a Service Design Approach - Figueiredo, Rejane; Venson, Elaine; Pedrosa, Glauco; Gardenghi, John; Judice, Marcelo; Judice, Andrea; Costa, Flavio (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Organizations have been seeking to adopt new work practices to become more flexible, adaptable, and quick in their responses to societal expectations. For the Transformation of Public Services, some of these new practices include Agile Governance for management, agile principles and methods, and the use of Service Design (SD) as a human-centered approach, employing co-design and co-creation. SD has been developed and improved in various areas and contexts; however, its adoption in the Human-Computer Interaction (HCI) field is still in its early stages. This work aims to contribute to the HCI field by presenting the use of SD in three projects of a Brazilian government body, from the strategic level to the reflection of solutions, using collaborative approaches, methods, and techniques. The inherent principles of SD that influenced stakeholder interaction and the design of digital services are presented and discussed. The results obtained show that SD makes it possible to promote more intuitive, efficient, and citizen-centered experiences, while also aligning with the needs of the body's stakeholders. Due to its holistic view, SD allows HCI professionals to consider not only the interaction itself but also the entire service context in which it occurs, ensuring that digital solutions are designed within a broader context, encompassing the problems, needs, and expectations of those involved and the citizens.